Comparison of certain blood values of coaches of national boxing team before and after matches - Pala, Ragip; Çinar, Vedat; Kiliç, Yakup; Karada?, Mustafa; Alpay, Numan; Orhan, Serdar (My University, 2013)
24 male coaches, who train national boxing teams of big male boxers (12) and big female boxers (12) and in the age range 27-56, constitute the research material. Blood samples of coaches in the research group were taken twice being before and after the matches. Data and laboratory results were utilized as covariant. Relative changes in the data obtained were analyzed in the SAS package program by utilizing PROC MEANS procedure. Significance level of differences between two measurements is determined by means of Paired t test that adds significance in the level of P<0.05. Statistically significant difference is observed in the Glucose levels of coaches as one of the blood parameters before and after the matches (P=0, 0365). Difference is seen in the values of insulin levels before and after the matches, however this difference is not found statistically significant (P=0, 7135). Statistically significant increase is found in the cortisol levels before and after matches (P<0, 001). Decrease is determined in the values of urea levels before and after the matches, however the difference in between is not found significant. (P=0, 0594). The decrease specified in the creatine levels before and after the matches is not found to be significant (P=0, 0745). In reference to the results of the study, it may be stated that significant changes are observed in the glucose and cortisol levels of coaches of national boxing team according to the measurements taken before and after matches.
Keywords: Blood; Coach; Cortisol; Creatine; Glucose; Insulin; Urea